Cluster-based supplier segmentation: A sustainable data-driven approach - Mohammad Rahiminia; Jafar Razmi; Sareh Shahrabi Farahani; Ali Sabbaghnia (Modern Supply Chain Research and Applications, 2023)
Purpose - Supplier segmentation provides companies with suitable policies to control each segment, thereby saving time and resources. Sustainability has become a mandatory requirement in competitive business environments. This study aims to develop a clustering-based approach to sustainable supplier segmentation. Design/methodology/approach - The characteristics of the suppliers and the aspects of the purchased items were considered simultaneously. The weights of the sub-criteria were determined using the best-worst method. Then, the K-means clustering algorithm was applied to all company suppliers based on four criteria. The proposed model is applied to a real case study to test the performance of the proposed approach. Findings - The results prove that supplier segmentation is more efficient when using clustering algorithms, and the best criteria are selected for sustainable supplier segmentation and managing supplier relationships. Originality/value - This study integrates sustainability considerations into the supplier segmentation problem using a hybrid approach. The proposed sustainable supplier segmentation is a practical tool that eliminates complexity and presents the possibility of convenient execution. The proposed method helps business owners to elevate their sustainable insights.
Keywords: 650; Clustering; Purchasing portfolio matrix; Supplier management; Supplier potential matrix; Sustainability